Consolidation chemotherapy in postmolar low-risk gestational trophoblastic neoplasia: a systematic review protocol. Issue 2 (24th February 2022) - Branco-Silva, Mariza; Maesta, Izildinha; Elias, Kevin; Berkowitz, Ross Stuart; Abbade, Joelcio Francisco; Horowitz, Neil S
Abstract : Introduction: Current evidence remains insufficient to strongly demonstrate the benefits of consolidation chemotherapy to all women with low-risk gestational trophoblastic neoplasia (GTN). This protocol outlines a systematic review to investigate whether consolidation chemotherapy is necessary for all patients with postmolar low-risk GTN after human chorionic gonadotropin normalisation with first-line single-agent chemotherapy. Methods and analysis: A search string will be used to search the PubMed (MEDLINE), EMBASE, Web of Sciences, Scopus, LILACS and Cochrane Central Register of Controlled Trials databases. Articles will be screened at the title and abstract level, and then at the full article level by two independent reviewers using inclusion/exclusion criteria. Randomised and non-randomised study designs will be included, while case studies, commentaries, editorials, review articles, animal studies, basic science studies and cross-sectional studies, as well as studies not reporting relapse/recurrence rates and/or whether consolidation chemotherapy was delivered will be excluded. There will be no restrictions on date of publication, geographical location, study setting, or language of publication. The primary outcome is rate of recurrence/relapse. The assessments of randomised controlled trials will be performed using the risk of bias tool from the Cochrane Collaboration. Non-randomised studies will be assessed using the Newcastle-Ottawa scale. The quality of evidence will be assessed using the Grading quality of evidence and strength of recommendations (Grades of Recommendations, Assessment, Development and Evaluation) guidelines. Ethics and dissemination: No formal ethical approval is required as all data collected will be secondary data and analysed anonymously. Results will be disseminated through a peer-reviewed publication and at scientific events. PROSPERO registration number: CRD42020164822.